Mesenchymal stromal cell delivery of oncolytic immunotherapy improves CAR-T cell antitumor activity - McKenna, Mary K. (Mol Ther, 2021)
The immunosuppressive tumor microenvironment (TME) is a formidable barrier to the success of adoptive cell therapies for solid tumors. Oncolytic immunotherapy with engineered adenoviruses (OAd) may disrupt the TME by infecting tumor cells, as well as surrounding stroma, to improve the functionality of tumor-directed chimeric antigen receptor (CAR)-T cells, yet efficient delivery of OAds to solid tumors has been challenging. Here we describe how mesenchymal stromal cells (MSCs) can be used to systemically deliver a binary vector containing an OAd together with a helper-dependent Ad (HDAd; combinatorial Ad vector [CAd]) that expresses interleukin-12 (IL-12) and checkpoint PD-L1 (programmed death-ligand 1) blocker. CAd-infected MSCs deliver and produce functional virus to infect and lyse lung tumor cells while stimulating CAR-T cell anti-tumor activity by release of IL-12 and PD-L1 blocker. The combination of this approach with administration of HER.2-specific CAR-T cells eliminates 3D tumor spheroids in vitro and suppresses tumor growth in two orthotopic lung cancer models in vivo. Treatment with CAd MSCs increases the overall numbers of human T cells in vivo compared to CAR-T cell only treatment and enhances their polyfunctional cytokine secretion. These studies combine the predictable targeting of CAR-T cells with the advantages of cancer cell lysis and TME disruption by systemic MSC delivery of oncolytic virotherapy: incorporation of immunostimulation by cytokine and checkpoint inhibitor production through the HDAd further enhances anti-tumor activity.